CLINICAL RESEARCH FOR WOMEN SUFFERING FROM INFERTILITY - Sayfutdinova Z. A.; Safarova G.A (Scholar Express Journals, 2025)
The aim of the study was to identify risk factors for infertility in women diagnosed with chronic endometriitis (CE) and to examine their impact on reproductive health. Chronic endometritis is an important gynecological condition causing infertility in women and requires deeper analysis in the context of its association with reproductive problems. The study involved two groups: 25 women with CE and infertility and 10 healthy women in the control group. The methods used included sociological and gynecological analyses, biopsy, hysteroscopy, Dopplerography and statistical analysis. The results showed that women with CE had a high level of hormonal disorders such as hypermenstrual syndrome and dysmenorrhea, as well as a higher prevalence of chronic diseases such as thyroid disease and chronic tonsillitis. An important factor is early diagnosis of CE, which contributes to improved treatment and prevention of infertility. The study emphasizes the importance of individual preparation for pregnancy and prevention of reproductive diseases to improve reproductive health
Keywords: Infertility; hyperhomocysteinemia; therapy